2019
DOI: 10.3390/proteomes7020015
|View full text |Cite
|
Sign up to set email alerts
|

More than a Toxin: Protein Inventory of Clostridium tetani Toxoid Vaccines

Abstract: Clostridium tetani is the etiological agent of tetanus, a life-threatening bacterial infection. The most efficient protection strategy against tetanus is a vaccination with the C. tetani neurotoxin, which is inactivated by formaldehyde-crosslinking. Since we assumed that besides the tetanus toxin, other proteins of C. tetani may also be present in toxoid preparations, we analyzed commercially available vaccines from different countries in respect to their protein content using mass spectrometry. In total 991 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…After considering the nature of bacterial vaccines, we discarded conjugate and polysaccharides vaccines and sought for potential sources of cross-reactive immunity in antigens identified by proteomics in DTa/wP and MenB vaccines. D and T antigens can vary between different vaccines, and here we considered the sum of all those reported elsewhere in (13,14,49). Our results, summarized in Table 4, indicate that combination DTP vaccines are significant sources of B and T cell cross-reactivity to SARS-CoV-2, while such cross-reactivity is small from MenB vaccine.…”
Section: Cross-reactive Immunity To Sars-cov-2 From Bacterial Vaccinementioning
confidence: 81%
See 1 more Smart Citation
“…After considering the nature of bacterial vaccines, we discarded conjugate and polysaccharides vaccines and sought for potential sources of cross-reactive immunity in antigens identified by proteomics in DTa/wP and MenB vaccines. D and T antigens can vary between different vaccines, and here we considered the sum of all those reported elsewhere in (13,14,49). Our results, summarized in Table 4, indicate that combination DTP vaccines are significant sources of B and T cell cross-reactivity to SARS-CoV-2, while such cross-reactivity is small from MenB vaccine.…”
Section: Cross-reactive Immunity To Sars-cov-2 From Bacterial Vaccinementioning
confidence: 81%
“…In contrast, vaccines for N. meningitides serotype B (MenB) consist of surface proteins from N. meningitides (15). Diphteria (D) and tetanus (T) vaccines contain inactivated toxins produced by the bacteria (toxoids) but in addition include a large array of proteins as shown by proteomics studies, which can be immunogenic (14,49). D and T antigens are generally combined with pertussis (P) antigens as a combination DTP vaccine, which is available in two main formulations: DTaP and DTwP.…”
Section: Cross-reactive Immunity To Sars-cov-2 From Bacterial Vaccinementioning
confidence: 99%
“…Current CITT vaccines are clinically effective but are crude and contain varied amounts of CITT (7). Mass spectrometric analyses of five human CITT vaccines identified 991 C. tetani proteins, of which 206 proteins were common to the five vaccines (7).…”
Section: Discussionmentioning
confidence: 99%
“…3) (0.1 g in alum) followed by one boost of 8MTT or CITT (0.1 g in alum). Enzyme-linked immunosorbent assay (ELISA) assessment of IgG in blood collected at Przedpelski et al 7 days postboost showed that 8MTT and CITT elicited similar IgG responses to those of the antigens used in the ELISA, which included TT Ͼ light chain (LC) linked to the translocation domain (HCN) (LCHCN) ϭ HCC Ͼ LC. Six of eight mice vaccinated with one boost of 8MTT and five of eight mice vaccinated with one boost of CITT survived challenge by 10,000ϫ LD 50 i.p.…”
Section: Properties Of 8mttmentioning
confidence: 99%
See 1 more Smart Citation